Segregating Sound : Inventing Folk and Pop Music in the Age of Jim Crow - Miller, Karl Hagstrom, 1968- (Book collections on Project MUSE., 2010)
Asks how the racialized genre divisions in American commerical music came into being, and how they became so entrenched, challenging the assumption of strict musical segregation in the late-19th-century rural South.